An Improved Protocol for Extraction and RT-PCR Detection of Citrus Viroids - Bernad, Lucia; Durán-Vila, Núria (IOCV, 2021)
The great sensitivity of RT-PCR makes this technique a desirable alternative to other diagnostic methods for detection of viroids. In previous studies, difficulties have been encountered in obtaining amplicons from samples known to contain viroids. The aim of the present study was to minimize extraction procedures and to design RT-PCR protocols based on the use of thermostable reverse transcriptases. The use of 27-nucleotide primers and reverse transcription at 60°C minimized renaturation of the viroid template and consistently yielded the expected PCR products for each viroid. The protocol has been tested with samples from a large number of viroid-host combinations grown under greenhouse conditions as well as with samples from the field.